2012
DOI: 10.1111/j.1439-0426.2012.01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserving young-of-the-yearPerca fluviatilisin ethanol, formalin, or in a frozen state and the consequences for measuring morphometrics

Abstract: As it is often not possible to immediately analyse individuals sampled in the field, captured fish are preserved and stored for later investigation. The objective of this study was to assess the effects of various preservation methods on subsequent changes in morphometric parameters while also providing correction factors to re-calculate the original body dimensions when sampled fish are measured at a later date. In this study, juvenile perch (Perca fluviatilis, 66.5 ± 10.2 mm total length) were measured direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…Traditionally, formalin has been used to preserve marine benthos [11]. Formalin preservation acts by fixing proteins through binding to peptide linkages, which preserves morphological structure but also acts to degrade DNA [12][13] Ethanol is the most common preservative for freshwater biomonitoring programs [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, formalin has been used to preserve marine benthos [11]. Formalin preservation acts by fixing proteins through binding to peptide linkages, which preserves morphological structure but also acts to degrade DNA [12][13] Ethanol is the most common preservative for freshwater biomonitoring programs [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…measurements taken immediately after capture). König and Borcherding () reported that whole‐body morphology of frozen fish differed the least from fresh fish, and that most changes occurred within a few days of preservation in all methods. Although much higher than for other methods, the reported P‐value for manova of Canonical Variate Analysis scores used to assess changes in whole‐body morphology was still significant after 54 days frozen, demonstrating changes in overall morphology induced by freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Although much higher than for other methods, the reported P‐value for manova of Canonical Variate Analysis scores used to assess changes in whole‐body morphology was still significant after 54 days frozen, demonstrating changes in overall morphology induced by freezing. König and Borcherding () ultimately concluded freezing should be a ‘standard preservation technique for fish intended for morphometric analysis (p. 743).’…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined data set contained measurements of brain and body mass made on both fresh tissue and formalin-fixed samples, using a range of preservation and storage methods (ethanol, formalin, or phosphate buffer), some of which had been stored in 70% ethanol for up to 65 years. Most studies on the effects of fixation and preservation on aquatic vertebrates have shown that both body mass and length undergo significant changes following fixation and storage in various media [Shields and Carlson, 1996;Kristoffersen and Salvanes, 1998;Buchheister and Wilson, 2005;König and Borcherding, 2012]. This applies to both larval and adult lampreys, in which differences of 3-6% have been recorded between fixed and fresh tissues [Stähler, 1982;Neave et al, 2006].…”
Section: Data Collectionmentioning
confidence: 99%